BLUE - COLLAR WORKERS LIKELIER TO OPPOSE SMOKING BANS - HAGE,DAVE (Tufts Archival Research Center, 2007)
Newspaper article describing the varied response of blue and white collar workers to anti-smoking policy. Theorizes that blue collar workers may be less responsive because of peer pressure, labor-management relations and/or thoughts about health and the future. Emphasizes the correlation between education level and smoking. Cautions the danger of generalizing about either set of workers and their motivations for smoking or not smoking.